The IMPLEMENTATION OF THE PARIS AGREEMENT IN POLAND. THEORY AND PRACTICE - Nawrot, Filip Karol; Radecka, Ewa (Review of European and Comparative Law, 2019)
The main aim of this paper is to describe the legal instruments of climate protection in Poland. This issue is significant, because for several decades, climate changes and climate protection have been the object of legal regulation, both international, European and domestic. The conducted analysis concerns three main legal acts: the Act of 27 April 2001 – Environmental Protection Law, the Act of 9 June 2011 – the Geological and Mining Law as regards CCS, and the Act of 20 February 2015 on Renewable energy (including, to a certain extent, regulations of the Act of 20 May 2016 on Investments in wind power plants). The paper closes with evaluation of present regulations and formulation of de lege ferenda proposals.